Linguopragmatic Analysis of Obsolete and Contemporary Slangisms in Young Adult Literature - Yakhyoeva, Gulkhumor Shukhrat kizi (The Lingua Spectrum, 2026)
This article examines the diachronic dynamics of slang units in the Young Adult (YA) literary genre from a linguopragmatic perspective. The study aims to identify the semantic, functional, and pragmatic differences between obsolete and current slangisms based on English-language YA novels published between 2000–2010 and 2018–2024. The findings indicate that the process of slang obsolescence takes an average of 8–12 years, while contemporary slangisms form more rapidly under the influence of digital communication and social media, and likewise fall out of use faster. The article also reveals the time lag between slang stylization in YA literature and its actual occurrence in spoken discourse. Furthermore, the study examines the pragmatic functions of slang units in expressing intergenerational linguistic differences, constructing the social identity of young characters, and ensuring the authenticity of fictional dialogues. By comparing slang units used in YA works produced during different periods, the study identifies tendencies in their semantic renewal, expansion or narrowing of meaning, as well as changes in their pragmatic functions. Particular attention is paid to the influence of the contemporary digital environment, especially social media, messaging platforms, memes, and online communities, on youth vocabulary.